Determination of reference ranges for normal upper trapezius elasticity during different shoulder abduction using shear wave elastography: a preliminary study - Wang, Lei (Sci Rep, 2020)
The purpose of this study was to determine the reference ranges of normal upper trapezius (UT) elasticity during different shoulder abduction using shear wave elastography (SWE). Mean shear wave velocity (SWV) of UT elasticity in eighty healthy participants were measured at left and right shoulder 0° abduction and 90° passive abduction (L0°, R0°, L90°, R90°) with SWE. The effects of potential factors (gender, UT thickness, age, and body mass index) on UT elasticity were analyzed. The reference ranges of normal UT elasticity were calculated by using the normal distribution method. UT elasticity was significantly different among various shoulder abduction (P < 0.0001). UT elasticity was significantly higher in males at both L90° (P < 0.05) and R90° (P < 0.01) than in females. The reference ranges of normal UT elasticity were 2.90–4.01 m/s at L0° and 3.01–4.29 m/s at R0°, and were 4.90–6.40 m/s in males and 4.40–6.20 m/s in females at L90°, 5.20–7.02 m/s in males and 4.71–6.80 m/s in females at R90°. Our results suggest that gender should be considered when determining the reference ranges of normal UT elasticity at L90° and R90° with SWE. These values may provide quantitative baseline measurements for the assessment of UT muscle strain in the future.